PENGARUH VARIASI GROUND BUSI DAN PUTARAN MESIN PADA KONVERSI BAHAN BAKAR MOTOR BENSIN KE BAHAN BAKAR LPG TERHADAP EMISI GAS BUANG MESIN POMPA AIR 200 CC : THE EFFECT OF SPARK PLUG GROUND VARIATION AND MACHINE ROTATION ON CONVERSION OF GASOLINE MOTOR FUEL TO LPG FUEL ON EXHAUST EMISSIONS OF 200CC WATER PUMP ENGINE - Achsani Taqwim (Jurnal Teknik Mesin, 2024)
Exhaust emissions are the residual combustion of fuel in the engine that is released through the engine exhaust system. Gasoline water pumps have emissions that have a negative impact on the environment. To overcome this problem, this research modified the fuel system from Pertalite fuel to LPG fuel. The purpose of fuel conversion is to reduce air pollution and prove that LPG fuel exhaust gas is better than Pertalite, so it is necessary to test exhaust gas emissions. Exhaust Gas Analizer test method, measure exhaust gas emission levels rpm 1,500, 2,000, 2,500, 3,000 and ground spark plug variations 1, 3, 4 include gas CO, HC, Duration of 60 seconds, record the emission levels of Pertalite and LPG fuels. The results of the analysis of exhaust emissions testing that have been carried out show that exhaust emissions from LPG fuel are not better than exhaust emissions from Pertalite fuel.